2010
DOI: 10.1007/s10457-010-9310-2
|View full text |Cite
|
Sign up to set email alerts
|

Sediment, nutrient and water losses by water erosion under agroforestry systems in the semi-arid region in northeastern Brazil

Abstract: Inadequate soil management practices adopted in the Brazilian semi-arid region contribute to erosive processes. Agroforestry systems (AFs) have been considered an alternative to reduce water erosion. This study aimed to evaluate the impact of two alternatives AFs, a traditional and an intensive cropping system on the losses of sediments, water, organic carbon and nutrients caused by water erosion in comparison to the natural vegetation (caatinga) in a semi-arid region of northeastern Brazil. The agroecosystems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 21 publications
2
21
0
4
Order By: Relevance
“…In the experimental area (3°41'S, 40º20'W), the average annual rainfall over the past 10 years was 989 mm. The soil in the area consists of patches of typical Ortic Chromic Luvisol and typical Hypochromic Luvisol (AGUIAR et al, 2010). The vegetation is a thorny deciduous savannah, regionally known as Caatinga (COLE, 1960).…”
Section: Description Of the Study Area And Management Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the experimental area (3°41'S, 40º20'W), the average annual rainfall over the past 10 years was 989 mm. The soil in the area consists of patches of typical Ortic Chromic Luvisol and typical Hypochromic Luvisol (AGUIAR et al, 2010). The vegetation is a thorny deciduous savannah, regionally known as Caatinga (COLE, 1960).…”
Section: Description Of the Study Area And Management Systemsmentioning
confidence: 99%
“…Studies by Aguiar et al (2010), Iwata et al (2012), Maia et al(2006;, Nogueira et al (2008), and Silva et al (2011) demonstrated the beneficial effects of agroforestry systems on the soil chemical, physical and biological properties, as well as on the preservation of the plant diversity (ALMEIDA et al, 2009;CAMPANHA et al, 2011). Some of the above studies were developed in experimental areas of the National Goat and Sheep Research Center (CNPCO), in the northern part of the Ceará State, Brazil, where agroforestry systems are being studied as an alternative to the traditional management of family farming.…”
Section: Introductionmentioning
confidence: 99%
“…Solo, 35:1597Solo, 35: -1608Solo, 35: , 2011 In the semi-arid Northeastern region of Brazil, AGF may be considered a promising alternative to restore the soil quality of areas degraded by intense soil cultivation (Araújo Filho & Carvalho, 2001). These agroecosystems can improve nutrient cycling and enhance soil structure (Maia at al., 2006), reducing water erosion (Aguiar et al, 2010) and increasing soil organic C stocks (Maia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…O sistema iLPF auxilia no aumento das interações biológicas entre os cultivos agrícolas, árvores e animais e reduz os riscos de erosão mantendo ou elevando os estoques de matéria orgânica quando comparado com outros modelos agrícolas (AGUIAR et al, 2010;MOLUA, 2005). Outra importante opção é o sistema Santa Fé pelo cultivo de culturas anuais, especialmente o milho, consorciado com forrageiras, principalmente as do gênero Brachiaria.…”
Section: Introductionunclassified